Unveiling the Mary Macha Archives - Suzanne Spunner (Archives & Manuscripts, 2019)
Perth-based art dealer Mary Macha was engaged with Indigenous art for almost fifty years. She played a critical role in the development of Aboriginal art in Western Australia firstly in the government sector and subsequently as a private dealer. Her clients included Alistair McAlpine (Lord McAlpine) and Robert Holmes a Court. She was the key player in the development of what became known as the East Kimberley School of art and formed a close relationship with the key artists, Paddy Jamanji and Rover Thomas. After her death in 2017, her archive was sorted and collated by her executors with assistance from the University of Melbourne and vested with the Battye Library in Perth.